Poster media on the subject of Al-Qur'an Hadith in increasing students' learning motivation - Aziz, Mursal; Ashshiddiqi, M. Hasbie; Sakinah, Siti (Univeritas Papua, 2024)
This research aims to describe the use of poster media in Al-Qur'an and Hadith subjects in increasing student learning motivation at MIS Islamiyyah Londut North Labuhanbatu. This research uses descriptive qualitative research methodology. Qualitative research methods are used as research techniques that produce descriptive data. Data collection techniques used include observation, interview and documentation. Research findings show that the use of poster media in Al-Qur'an and Hadith subjects is carried out using a violent approach. This method involves the teacher being in front of the class, using visual aids such as posters. The teacher continues by explaining the contents of the poster sequentially and step by step. Students show a level of enthusiasm and excitement in the learning process in class because the learning material is presented with visuals that are relevant to the Al-Qur'an and Hadith subjects they are studying. In the context of using poster media in learning the Qur'an and Hadith, observations show several clear signs of how students become more motivated, including: Increased student enthusiasm, students are more active, increasing students' curiosity. The use of poster media shows that students' enthusiasm and motivation for learning has increased, because they prefer to use visual aids, such as photos, when teaching, rather than just relying on verbal material.